Sexual Social Scripts and the re-Imaginings of Community Identity - Fowler, Maria (Ethnologies, 2001)
Drawing from research undertaken at the Michigan Womyn’s Music Festival in 1997 and 1998, this article explores some of the sociospatial complexities inherent within the queer discourses, performances, and significations of “home” and “homecoming” that play out at the annual event. Paying particular attention to the relationship between the discursive space of the queer “social imaginary” — one which seeks to resist the hegemony of heteronormative sexual social scripts — and the physical space of the Michigan Womyn’s Music Festival, the author considers the ways in which notions and deployments of sameness and difference, inclusion and exclusion, and community consolidation and contestation mark the annual event.